2021
DOI: 10.7150/jca.52329
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic factors are associated with the prognosis of Thyroid Cancer

Abstract: Background: Thyroid adenomas/adenocarcinomas are the most common type of thyroid cancer. The impact of socioeconomic factors on the prognosis of thyroid cancer is unclear. Methods: Clinical information and socioeconomic factors were obtained from the Surveillance, Epidemiology, and End Results Database (SEER) 18 Registries Custom Database. The association between thyroid adenomas/adenocarcinomas and socioeconomic factors including gender, race/ethnicity, insurance status, marital status, living area, and Yost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Compared with TT, one-sided thyroid LO plus IO or partial thyroidectomy also can achieve a good prognosis, which is of positive significance for guiding clinical practice. In recent years, some studies have revealed that marital status is closely related to the prognosis of TC (11,12,53) and married TC patients have a significant survival advantage. A study from 126,160 patients with all types of TC showed that widowed or divorced patients were closely related to poor CSS and overall survival (OS) (11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with TT, one-sided thyroid LO plus IO or partial thyroidectomy also can achieve a good prognosis, which is of positive significance for guiding clinical practice. In recent years, some studies have revealed that marital status is closely related to the prognosis of TC (11,12,53) and married TC patients have a significant survival advantage. A study from 126,160 patients with all types of TC showed that widowed or divorced patients were closely related to poor CSS and overall survival (OS) (11).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some studies have revealed that marital status is closely related to the prognosis of TC (11,12,53) and married TC patients have a significant survival advantage. A study from 126,160 patients with all types of TC showed that widowed or divorced patients were closely related to poor CSS and overall survival (OS) (11). Shi et al explored 61077 DTC patients and found that widowed patients had a higher tumor mortality in DTC (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As it is, the Yost index is a valuable covariate that improves model fit or helps to explain relationships between SES and healthcare and/or outcomes (Butler et al 2020, Li et al 2021, Liu et al 2021); however, the Yost Index is based on a statistically unreliable one-factor structure with unbalanced weights. Inclusion of low weighted indicators (e.g., working class, unemployment, education) gives the impression that those indicators do little to predict the latent variable; however, if all relevant factors are considered, they are influential.…”
Section: Discussionmentioning
confidence: 99%
“…One such index is the Yost Index, developed from a factor analysis of seven variables or combinations of variables from the American Community Survey (ACS) of the United States Census related to household income, poverty, rent, house value, education, employment type and employment status ( Yost et al 2001 ; Yu, Tatalovich, Gibson, & Cronin, 2014 ). Most of its applications have been in cancer surveillance ( Abdel-Rahman, 2019 ; Li et al, 2021 ; Rajeshuni et al, 2020 ; Ross et al, 2017 ; Swords, Mulvihill, Brooke, Firpo, & Scaife, 2020 ), and it is endorsed by the Surveillance, Epidemiology and End Results (SEER) program of the National Cancer Institute ( National Cancer Institute, 2021 ).…”
Section: Introductionmentioning
confidence: 99%